Smithian platform-bearing gondolellid conodonts from Yiwagou Section, northwestern China and implications for their geographic distribution in the Early Triassic. (23rd January 2019) - Li, Hanxiao; Jiang, Haishui; Chen, Yanlong; Wignall, Paul B.; Wu, Baojin; Zhang, Zaitian; Zhang, Muhui; Ouyang, Zhumin; Lai, Xulong
Abstract: Abundant platform-bearing gondolellid conodonts, including Scythogondolella mosheri (Kozur and Mostler), Sc . phryna Orchard and Zonneveld, and Sc . cf. milleri (Müller), have been discovered from the Yiwagou Section of Tewo, together with Novispathodus waageni waageni (Sweet) and Nv . w . eowaageni Zhao and Orchard. This is the first report of Smithian platform-bearing gondolellids from the Paleo-Tethys region. In addition, Eurygnathodus costatus Staesche, E . hamadai (Koike), Parafurnishius xuanhanensis Yang et al., and the genera Pachycladina Staesche, Parachirognathus Clark, and Hadrodontina Staesche have also been recovered from Dienerian to Smithian strata at Yiwagou Section. Three conodont zones are established, in ascending order: Eurygnathodus costatus - E . hamadai Assemblage Zone, Novispathodus waageni - Scythogondolella mosheri Assemblage Zone, and the Pachycladina - Parachirognathus Assemblage Zone. The platform-bearing gondolellids were globally distributed just after the end-Permian mass extinction, but the formerly abundant Clarkina Kozur disappeared in the late Griesbachian. Platform-bearing gondolellids dramatically decreased to a minimum of diversity and extent in the Dienerian before recovering in the Smithian. Scythogondolella Kozur, probably a thermophilic and eurythermic genus, lived in all latitudes at this time whereas other genera did not cope with Smithian high temperatures and so became restricted to the high-latitude regions. However, the maximum temperature in the late Smithian likely caused the extinction of almost all platform-bearing gondolellids. Finally, the group returned to equatorial regions and achieved global distribution again in the cooler conditions of the late Spathian. We conclude that temperature (and to a lesser extent oxygen levels) exerted a strong control on the geographical distribution and evolution of platform-bearing gondolellids in the Early Triassic.